Antidimentia activity of instant granule containing a combination of Brassica oleracea L. Var. Italica and Centella asiatica L. Urban extracts in male mice (Mus musculus) model of dementia - Erni Rustiani; Suci Sintya; Min Rahminiwati (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2025)
Dementia is a progressive cognitive impairment characterized by cognitive decline and memory loss. Acetylcholine levels in dementia patients decrease due to increased levels of acetylcholinesterase which breaks down acetylcholine into choline and acetate. Gotu kola (Centella asiatica L. Urban) contains asiaticoside,while broccoli (Brassica oleracea L. Var Italica) contains glucosinolate. Both compounds are believed to have acetylcholinesterase inhibitor activity. This study aimed to evaluate the antidementia activity of instant granules of a combination of B. oleracea and C. asiatica extracts in male white mice model of dementia. Thirty-five male mice were used in this experimental divided into seven group with five mice in each group. All groups were induced with hyoscine butylbromide intraperitoneally except the normal control group (group I). Group II (negative control) was given Na CMC 0.5% orally, and group III (positive control) was given piracetam intraperitoneally. Groups IV to VII were given instant granules with different formulation, namely namely group IV (25 mg :190 mg dose 1x), group V (25 mg : 190 mg dose 2x), group VI (190 mg : 190 mg dose 1x) and group VII (190 mg : 190 mg dose 2x). Y-maze test for mice was carried out for 5 min by allowing mice to explore the three arms of the Y-maze freely. A significant difference in antidementia activity between groups given the instant granules was observed (p <0.05). The instant granules combination with a ratio of B. oleracea andC. asiatica extracts (190 mg : 190 mg) had a higher antidementia activity than that combination of 25 mg : 190 mg. The instant granules combination with a ratio of B. oleracea and C. asiatica extracts (190 mg : 190 mg) at dose 2x had a higher antidementia activity than at dose 1x. In conclusion, the instant granules combination of B. oleracea and C. asiatica have a potential antidementia activity.